Nkx2.2 regulates cell fate choice in the enteroendocrine cell lineages of the intestine - Desai, Shailey (2007)
Nkx2.2 is a homeodomain-containing transcription factor essential for pancreatic islet cell specification. In this study we investigate the role of Nkx2.2 within the small intestine. We have determined that Nkx2.2 is expressed at the onset of intestinal epithelial cell differentiation in specific intestinal cell populations, including a subset of enteroendocrine cells. Similar to its role in the pancreatic islet, Nkx2.2 regulates cell fate choices within the intestinal enteroendocrine population; in the Nkx2.2 null mice, several hormone-producing enteroendocrine cell populations are absent or reduced and the ghrelin-producing cell population is upregulated. The remaining intestinal cell populations, including the paneth cells, goblet cells and enterocytes appear to be unaffected by the loss of Nkx2.2. Furthermore, similar to the pancreatic islet, Nkx2.2 appears to function upstream of Pax6 in regulating intestinal cell fates; Pax6 mRNA and protein expression is decreased in the Nkx2.2 null mice. These studies identify a novel role for Nkx2.2 in intestinal endocrine cell development and reveal the regulatory similarities between cell type specification in the pancreatic islet and in the enteroendocrine population of the intestine.